Beam Energy Scan of Specific Heat Through Temperature Fluctuations in Heavy Ion Collisions. (January 2016) - Basu, Sumit; Nandi, Basanta K; Chatterjee, Sandeep; Chatterjee, Rupa; Nayak, Tapan
Abstract: Temperature fluctuations may have two distinct origins, first, quantum fluctuations that are initial state fluctuations, and second, thermodynamical fluctuations. We discuss a method of extracting the thermodynamic temperature from the mean transverse momentum of pions, by using controllable parameters such as centrality of the system, and range of the transverse momenta. Event-by-event fluctuations in global temperature over a large phase space provide the specific heat of the system. We present Beam Energy Scan of specific heat from data, AMPT and HRG model prediction. Experimental results from NA49, STAR, PHENIX, PHOBOS and ALICE are combined to obtain the specific heat as a function of beam energy. These results are compared to calculations from AMPT event generator, HRG model and lattice calculations, respectively.